Role of NF-E2 related factor 2 (Nrf2) on chemotherapy resistance in acute myeloid leukemia (AML) and the effect of pharmacological inhibition of Nrf2. - Sreeja Karathedath; Bharathi M Rajamani; Syed Mohammed Musheer Aalam; Ajay Abraham; Savitha Varatharajan; Partha Krishnamurthy; Vikram Mathews; Shaji Ramachandran Velayudhan; Poonkuzhali Balasubramanian (PLoS ONE)
Cytarabine (Ara-C) and Daunorubicin (Dnr) forms the backbone of acute myeloid leukemia (AML) therapy. Drug resistance and toxic side effects pose a major threat to treatment success and hence alternate less toxic therapies are warranted. NF-E2 related factor-2 (Nrf2), a master regulator of antioxidant response is implicated in chemoresistance in solid tumors. However, little is known about the role of Nrf2 in AML chemoresistance and the effect of pharmacological inhibitor brusatol in modulating this resistance. Primary AML samples with high ex-vivo IC50 to Ara-C, ATO, Dnr had significantly high NRF2 RNA expression. Gene-specific knockdown of NRF2 improved sensitivity to these drugs in resistant AML cell lines by decreasing the expression of downstream antioxidant targets of Nrf2 by compromising the cell's ability to scavenge the ROS. Treatment with brusatol, a pharmacological inhibitor of Nrf2, improved sensitivity to Ara-C, ATO, and Dnr and reduced colony formation capacity. AML cell lines stably overexpressing NRF2 showed increased resistance to ATO, Dnr and Ara-C and increased expression of downstream targets. This study demonstrates that Nrf2 could be an ideal druggable target in AML, more so to the drugs that function through ROS, suggesting the possibility of using Nrf2 inhibitors in combination with chemotherapeutic agents to modulate drug resistance in AML.